DEVELOPMENT OF NATURAL SCIENTIFIC THINKING OF STUDENTS WHEN STUDYING NATURAL DISCIPLINES - Манзій, О.П.; Плахотна, С.І. (Modern engineering and innovative technologies, 2023)
The article defines directions for improving the modern education system. It is emphasized that the schoolboy’s attitude to nature indicates the level of his natural and scientific thinking. The problem of subjective attitude to nature is considered. The